2000
DOI: 10.1136/heart.84.4.e8
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of aconitine induced life threatening ventricular tachyarrhythmia with amiodarone

Abstract: With the increasing trend of cross mixing of populations, aconitine induced poisoning and its related arrhythmias may be more frequently encountered worldwide. However, the clinical experience is often too limited to draw any conclusion on the optimal treatment for tachycardia induced by aconitine intoxication. The clinical presentation, serial electrocardiographic changes, and responses to antiarrhythmic agents are reported in a patient with aconitine induced life threatening ventricular tachyarrhythmia. Amio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…On the other hand, found that the intravenous injection of KBR significantly increased the doses of ouabain required to induce ventricular arrhythmias (PVC, VT, and VF) in anesthetized guinea pigs and concluded that KBR suppressed ouabaininduced arrhythmias through inhibition of NCX. Yeih et al (2000) reported recently a successful treatment of aconitineinduced life-threatening ventricular tachyarrhythmia by amiodarone in a clinical case. As amiodarone in therapeutic concentrations binds to many membrane/channel proteins (multichannel blocker) like KBR, their clinical results support our experimental results observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, found that the intravenous injection of KBR significantly increased the doses of ouabain required to induce ventricular arrhythmias (PVC, VT, and VF) in anesthetized guinea pigs and concluded that KBR suppressed ouabaininduced arrhythmias through inhibition of NCX. Yeih et al (2000) reported recently a successful treatment of aconitineinduced life-threatening ventricular tachyarrhythmia by amiodarone in a clinical case. As amiodarone in therapeutic concentrations binds to many membrane/channel proteins (multichannel blocker) like KBR, their clinical results support our experimental results observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Severe poisoning has been reported after consumption of decoctions prepared from prescriptions containing 6 g of cured Aconitum rootstocks (Chan and Critchley, 1996). The Aconitum toxicity is attributed to its toxic Aconitum alkaloids, including aconitine, mesaconitine, and hypaconitine (Yeih et al, 2000). For example, aconitine as one of the active ingredients exhibits severe toxicity in humans as well as in laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
“…(5) One of the ventricular arrhythmias that can present in aconite poisoning is bidirectional VT. (6,7) This is a rare ventricular dysrhythmia with beat-to-beat alternation of the frontal QRS axis. Bidirectional VT is a hallmark of severe digitalis toxicity and can also occur in cases of catecholaminergic polymorphic ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%